Development of switchless thin-plate type sorption compressor cell for 5 K sorption J-T refrigerator. (July 2020) - Bae, Junhyuk; Kwon, Dohoon; Jeong, Sangkwon
Highlights: A thin-plate type sorption compressor cell without a heat switch is fabricated. The experiment of adsorption between activated charcoal and helium is conducted. The experiment of cooling-down and heating-up the cell are conducted. The prediction model is constructed and validated by experiment results. The cooling capacity of the refrigerator is calculated as 2.2 mW at 5 K. Abstract: A sorption J-T (Joule-Thomson) refrigerator is a J-T refrigerator using a sorption compressor that compresses refrigerant by adsorption and desorption in sorption cells. When the sorption cell of the compressor is cooled, the refrigerant is adsorbed on the adsorbent, reducing the pressure of the cell. In contrast, when the cell is heated, its pressure increases due to desorption of the refrigerant from the adsorbent. The sorption cells should operate in pairs to produce a continuous pressure gradient for J-T expansion since the cell can create pressure periodically. Therefore, to increase cooling capacity of the refrigerator, it is indispensable to reduce the cycle time by accelerating thermal response of the sorption cell. This paper suggests a thin-plate type sorption cell to maximize the heat diffusion to the adsorbent. Furthermore, because its temperature can be altered rapidly, the sorption compressor can operate without a heat switch to regulate heating and cooling of the sorption cell. The sorption cell is made of stainless steel 304 with width and length of 100 mm and height of 4.6 mm, respectively. The activated charcoal with two different nominal sizes is charged into the cell as an adsorbent of helium for cooling at 5 K. On the top and the bottom side of the cell, the cold head of G-M (Gifford-McMahon) refrigerator and the polyimide film heater are attached to adsorb and desorb helium in the cell, respectively. Its ability to build the pressure is verified by heating the cell which contains constant mass of helium. Furthermore, the mass of helium adsorbed on activated charcoal at various temperature are measured by expanding helium from a reservoir to the sorption cell to construct the precise prediction model. Subsequently, the operation parameters for sorption compressor are determined employing a prediction model which is validated by the cooling-down and the heating-up experiment. The predicted mass flow rate and the cycle time of the compressor are 2.37 mg/s and 55.4 s, respectively. Consequently, the cooling capacity of the sorption J-T refrigerator with recuperative heat exchanger is predicted as 2.2 mW at 5 K.